Return of the bison : a story of survival, restoration, and a wilder world - DiSilvestro, Roger L. (Mountaineers Books, 2023)
In less than a century, a bison population that once numbered in the millions and stretched across North America was reduced to just a few dozen animals primarily in Yellowstone National Park. DeSilvestro explores one of the greatest conservation comeback stories in American history-- yet its "success" is qualified. Most bison today live in commercial herds, contained like cattle. Are we willing to coexist with them as wild animals who need freedom to roam? -- adapted from back cover